The concept of illegal migration on the national and international levels and its distinction from other concepts - salah djeloud (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Migration, a long-standing human phenomenon, has grown complex due to social, economic, and political factors, impacting nations globally. In response, countries and international organizations have established legal frameworks to regulate migration, safeguarding human rights while enabling lawful movement. However, migration outside these legal boundaries is termed "illegal migration," overlapping with concepts like asylum, forced deportation, displacement, and expulsion. While all involve human movement, they differ in context. Domestic laws address these issues, forming the basis for international efforts through organizations and agreements to combat illegal migration and involuntary movement, mitigate risks, and protect rights. This paper aims to clarify illegal migration and differentiate it from related terms